CD4/CD8 Ratio Recovery of Children and Adolescents Living With HIV With Virological Suppression: A Prospective Cohort Study. (19th March 2020) - Han, Win Min; Apornpong, Tanakorn; Handoko, Ryan; Jantarabenjakul, Watsamon; Gatechompol, Sivaporn; Ubolyam, Sasiwimol; Kerr, Stephen J; Avihingsanon, Anchalee; Ruxrungtham, Kiat; Phanuphak, Praphan; Puthanakit, Thanyawee
Abstract: Background: There are limited data on immune restoration of young adults living with virologically suppressed human immunodeficiency virus (HIV). We investigated recovery rates of CD4/CD8 ratio among Thai children and adolescents after they initiated combination antiretroviral therapy (cART). Methods: Children and adolescents who started cART at age of ≥ 5 years were eligible in this study if they achieved HIV RNA < 50 copies/mL and had a CD4/CD8 ratio < 0.8 at the time of virological suppression. Normalization of CD4/CD8 ratio was defined as 2 consecutive values ≥ 1. Using group-based trajectory analysis, low- and high-recovery groups were identified in terms of CD4/CD8 ratio recovery. Results: One hundred thirty-eight children and adolescents (101 perinatally infected and 37 behaviorally infected) with median age of 10.6 years at cART treatment initiation were included. After 559 person-years of follow-up (PYFU), overall incidence rate of CD4/CD8 ratio normalization was 4.1 (95% confidence interval, 2.7–6.2) per 100 PYFU. The probabilities of normalization at 2, 5, and 10 years after HIV suppression were 5.2%, 22.6%, and 35.6%, respectively. The low-recovery group had lower median pre-cART CD4 count (146 vs 304 cells/μL, P  = .01), pre-cART CD4/CD8 ratio (0.15 vs 0.23, P  = .03) and at first viral suppression (0.38 vs 0.65, P  = .0001), compared to the high-recovery group. Conclusions: Less than half of children and adolescents living with HIV on cART with viral suppression had CD4/CD8 ratio normalization. Those with older age at cART initiation, lower pre-cART CD4 count, or CD4/CD8 ratio had slower ratio recovery. Long-term prognoses such as ongoing immune activation and clinical outcomes among children and adolescents on suppressive cART without CD4/CD8 ratio normalization need to be further investigated.